2022
DOI: 10.3390/ijms23158830
|View full text |Cite
|
Sign up to set email alerts
|

Facile Microwave Assisted Synthesis of Silver Nanostars for Ultrasensitive Detection of Biological Analytes by SERS

Abstract: We report a very simple, rapid and reproducible method for the fabrication of anisotropic silver nanostars (AgNS) that can be successfully used as highly efficient SERS substrates for different bioanalytes, even in the case of a near-infra-red (NIR) excitation laser. The nanostars have been synthesized using the chemical reduction of Ag+ ions by trisodium citrate. This is the first research reporting the synthesis of AgNS using only trisodium citrate as a reducing and stabilizing agent. The key elements of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Strapasson et al [ 101 ] used glycerol as a solvent and reducing agent and food-grade corn starch as a stabilizer to prepare silver nanoparticles by microwave radiation and the reaction principle is shown in Figure 6 a. The synthesis method was reproducible and the silver NPs synthesized after 320 days were highly stable as shown in Figure 6 b. Revnic et al [ 102 ] reported a very simple, rapid, and reproducible microwave-assisted preparation of anisotropic silver nanostars (AgNS), which consist of a central nanoparticle interconnected with several highly one-dimensional single arms having a star shape as shown in Figure 6 c,d. Microwave-assisted synthesis of nanostars was performed in sealed-bottom flasks at very short time intervals (less than 3 min), and the only chemical precursors in the wet chemistry procedure for synthesis were silver nitrate and trisodium citrate, and the plasma substrates synthesized by this method were able to produce strong SERS spectra.…”
Section: Synthesis Of Silver Nanostructurementioning
confidence: 99%
See 1 more Smart Citation
“…Strapasson et al [ 101 ] used glycerol as a solvent and reducing agent and food-grade corn starch as a stabilizer to prepare silver nanoparticles by microwave radiation and the reaction principle is shown in Figure 6 a. The synthesis method was reproducible and the silver NPs synthesized after 320 days were highly stable as shown in Figure 6 b. Revnic et al [ 102 ] reported a very simple, rapid, and reproducible microwave-assisted preparation of anisotropic silver nanostars (AgNS), which consist of a central nanoparticle interconnected with several highly one-dimensional single arms having a star shape as shown in Figure 6 c,d. Microwave-assisted synthesis of nanostars was performed in sealed-bottom flasks at very short time intervals (less than 3 min), and the only chemical precursors in the wet chemistry procedure for synthesis were silver nitrate and trisodium citrate, and the plasma substrates synthesized by this method were able to produce strong SERS spectra.…”
Section: Synthesis Of Silver Nanostructurementioning
confidence: 99%
“…Reprinted with permission from Ref. [ 102 ]. Copyright 2022, International Journal of Molecular Sciences.…”
Section: Synthesis Of Silver Nanostructurementioning
confidence: 99%
“…[ 25 ] A more recent report just used CIT as the reducing agent combined with microwave heating. [ 26 ] The AgNS produced via this approach have a very different morphology. Figure 1D shows a typical sample of AgNS.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is an inelastic scattering of light that interacts with the analyte [9]. Surface-enhanced Raman spectroscopy (SERS) is a variation in Raman spectroscopy in which the intensity of the vibrational Raman spectrum is highly amplified when the analyte is located in the very close vicinity of a plasmonic nanostructured surface [10][11][12]. SERS is a non-invasive method that can interrogate morphological changes in molecules of a sample by using minimal preparation and a small amount of sample [13].…”
Section: Introductionmentioning
confidence: 99%